1980
DOI: 10.1073/pnas.77.1.428
|View full text |Cite
|
Sign up to set email alerts
|

Protein bodies of mung bean cotyledons as autophagic organelles

Abstract: We present evidence that protein bodies constitute the principal lytic compartment in storage parenchyma cells of mung bean cotyledons and propose that they play a role in cellular autophagy. We developed a method to isolate protein bodies by incubating tissue slices with cell wall-degrading enzymes and fractionating the cellular organelles on a Ficoll gradient. About 75-80% of the protein bodies present in the protoplasts were recovered intact in a band at the 5/25% Ficoll interface. This band contained a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…It is worth noting in this context that protein bodies are part of the vacuolar/lysosomal compartment of plant cells. Recent evidence shows that protein bodies are derived from vacuoles during seed maturation (5,6,27) and that they contain numerous acid hydrolases (14,17,20,26). Protein bodies therefore have an enzymic complement and function similar to that of the central vacuole of plant cells or the lysosomes of animal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting in this context that protein bodies are part of the vacuolar/lysosomal compartment of plant cells. Recent evidence shows that protein bodies are derived from vacuoles during seed maturation (5,6,27) and that they contain numerous acid hydrolases (14,17,20,26). Protein bodies therefore have an enzymic complement and function similar to that of the central vacuole of plant cells or the lysosomes of animal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that PSVs have an ontogenetic relationship to the central vacuole has a long history (Hara and Matsubara, 1980;Van der Wilden et al, 1980;Melroy and Herman, 1991;Olbrich et al, 2007), but the general mechanism of the PSV-to-LV transformation Figure 9. Schematic diagram illustrating the different pathways involved in the transformation of PSVs into LVs in different types of root cells during seed germination and early root development.…”
Section: Cryofixation and Freeze-substitution Methods Are Important Fmentioning
confidence: 99%
“…Most likely, this sequence of events is designed to allow for the development of the vascular system before the amino acids are mobilized in the cotyledons and sent to the embryo axis cells (Tiedemann et al, 2001). During mobilization of the reserves, the PSVs become more acidic and acquire hydrolytic enzymes, and these physiological changes are accompanied by major changes in PSV structure (Ashton, 1976;Van der Wilden et al, 1980;Bethke et al, 1998;Tiedemann et al, 2000Tiedemann et al, , 2001Jiang et al, 2001, Saito et al, 2002He et al, 2007;Wang et al, 2007).…”
mentioning
confidence: 99%
“…In seeds, for example, protein storage vacuoles are formed during maturation while the proteins are degraded by the time of seed germination. 40 Data of Van der Wilden et al 41 and Herman et al 42 suggested that protein bodies enclose what seem to be autophagic vesicles. These vesicles carry acid hydrolases, including carboxypeptidase.…”
mentioning
confidence: 99%